Excellent Services by Frontliner Best Corporate Banking - Indira Diah Pitaloka; Chandra Hendriyani; Budiana Ruslan (JIP ( Jurnal Industri dan Perkotaan ), 2021)
Tight competition in the banking world requires every bank to be able to provide maximum service to each of its customers. To fulfill this, every bank strives to provide excellent service to each of its customers, Bank BRI is no exception. Bank BRI has Smart Service which is a guideline for excellent service, to overcome things that occur, especially frontliners who directly deal with customers.This study uses a phenomenological method with a qualitative approach where the subject in this study is BRI Bank and the object is customer service. This study aims to provide a detailed explanation of the implementation of Service Excellence. So that it can show the best corporate banking service.Based on the results of the study, it was found that the Smart Service from Bank BRI has met the criteria of excellent service (Barata, 2003 & Arasli et al, 2005) so that Smart Service from Bank BRI is a form of Best Corporate Banking from Bank BRI.